Analisis Kualitas Citra Steganografi Berbasis Spasial Pada Metode Least Significant Bits Dan Pixel Value Differencing - Masruri, Nizar Haris (Jurnal Pseudocode, 2025)
Steganography is a method in network security systems that functions to hide confidential information by inserting it into other media without changing the authenticity of the information. One of the steganography media is images. Image steganography has two domains: spatial and frequency. The spatial domain works on the pixels of an image, and the frequency domain works on the image frequency. Spatial image steganography is said to be good if the level of stego-image damage is very small. There are several intermediate methods in spatial steganography, namely: LSB, PVD, GLM, EBE, RPE, and others. However, there are two most popular methods, namely LSB (Least Significant Bit) and PVD (Pixel Value Differencing). Therefore, this study aims to test the quality of stego-images produced by these two methods. Testing is carried out using the MSE and PSNR value parameters. A stego-image is considered good when the MSE value is close to 0 and the PSNR value is above 30 dB. From the test data used, this study produced an MSE value of 0.0006 for LSB stego-images and 0.007 for PVD stego-images. The PSNR value was 90 dB for LSB stego-images and 72 dB for PVD stego-images. This study concluded that LSB stego-images have less damage than PVD stego-images, so the researchers recommend using the LSB method in carrying out the steganography process. Keywords: Spatial;MSE;PSNR;LSB;PVD